Standards, power, and market access: a political economy analysis of non-tariff measures and Indonesian cinnamon exports - Zulkifli, Lily Febriyanti; Kamarulzaman, Nitty Hirawaty; Ali, Hamed Norolla Bakheet; Nishantha, Busige; Tenriawaru, A. Nixia; Amir, Ayu Anisa; Syam, Siti Hardyanti; Darma, Rahim (Frontiers Media SA, 2026)
Indonesia is one of the world’s largest producers of cassia cinnamon; however, its export performance remains uneven despite its strong production capacity. This study examines how non-tariff measures—specifically, sanitary and phytosanitary (SPS) measures and technical barriers to trade (TBT)—alongside key macroeconomic factors, shape Indonesia’s cinnamon exports. Using a political economy framework, the analysis integrates panel data regression with revealed comparative advantage (RCA), export product dynamics (EPD), and X-model assessments across nine major destination markets from 2010 to 2024. The results show that SPS measures exert a significant trade-suppressing effect, functioning as exclusionary regulatory filters, whereas TBT compliance has a modest but positive enabling role. Importing countries’ income levels and population are negatively associated with export volume, indicating consumer upgrading to premium alternatives such as Ceylon cinnamon. The exchange rates and distance show limited explanatory power. These findings demonstrate that Indonesia’s export performance is shaped less by price competitiveness and more by regulatory power, institutional capacity, and shifting consumer preferences. Therefore, sustaining competitiveness requires a strategic shift from volume-based to value-based exports through quality upgrading, certification, traceability, and branding.